Bahasa yang Menjahit Identitas: Peran Bahasa Indonesia dalam Merancang Citra Produk Busana - Syahrani, Anggita; Bella Andriani,; Yulivia Tambun,; Bethia Chelsia Sembiring,; Dwi Sri Hartati,; Indah Rezky Karinata Br Sitepu,; Hendra Kurnia Pulungan, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The Indonesian language has a strategic position not only as a national communication tool, but also as an instrument that plays an important role in building the identity and image of local fashion products. Amidst the dominance of foreign languages in the fashion industry, the use of good, creative, and persuasive Indonesian language can differentiate and strengthen product branding. This study aims to examine the role of Indonesian in building the identity and image of fashion products, highlighting the strategy of using Indonesian slogans, phrases, and promotional narratives. The method used is a literature study by examining various journals, scientific articles, and relevant sources related to the role of language in branding and the creative economy. The results of the study show that Indonesian language can strengthen consumers' emotional appeal, increase trust in local brands, and emphasize cultural characteristics in fashion products. The case study of the Sejauh Mata Memandang brand shows how the use of typical Indonesian phrases, such as “Bumi Rumah Kita” (Our Home Earth) and “Kembali Baik” (Return to Goodness), has succeeded in creating emotional closeness with consumers while reinforcing cultural identity. Thus, Indonesian language not only functions as a medium of communication, but also as a strategic asset in building the image and competitiveness of the Indonesian fashion industry.